2007
DOI: 10.1065/espr2006.08.327
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inert dust on olive (Olea europaea L.) leaf physiological parameters

Abstract: Longterm effects of dust (from cement kiln or other sources) on olive leaf, plant productivity and nutritional quality of edible parts could be studied for conclusive results on dust contamination effects to perennial crops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
31
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 9 publications
5
31
1
6
Order By: Relevance
“…3B), similarly to results noted by Vardaka et al (1995) on the leaves of holm oak (Quercus coccifera L.). Similar results were also obtained by Nanos & Ilias (2007) when studying the effect of deposition of cement dust on the leaves of the European olive (Olea europaea L.). The smallest particles can clog stomata, thus reducing the concentration and accessibility of CO 2 independent of the effect on light phase of photosynthesis and transpiration (Naidoo & Chirkoot, 2004;Abdel-Rahman & Ibrahim, 2012;Burkhardt & Grantz, 2017).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…3B), similarly to results noted by Vardaka et al (1995) on the leaves of holm oak (Quercus coccifera L.). Similar results were also obtained by Nanos & Ilias (2007) when studying the effect of deposition of cement dust on the leaves of the European olive (Olea europaea L.). The smallest particles can clog stomata, thus reducing the concentration and accessibility of CO 2 independent of the effect on light phase of photosynthesis and transpiration (Naidoo & Chirkoot, 2004;Abdel-Rahman & Ibrahim, 2012;Burkhardt & Grantz, 2017).…”
Section: Discussionsupporting
confidence: 72%
“…In our study, P. serotina accumulated less PM on its leaves, which could protect it from the higher negative impact and could be another reason why this shrub is more tolerant to stressful conditions. Lowering the rate of photosynthesis due to the presence of PM accumulated on the surface of leaves can result from changes in the optical properties of the leaves and the decrease in radiation reaching the chlorophyll antenna, due to absorption or reflection by PM (Nanos & Ilias, 2007;Chauhan, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, cement kiln dust reduced 73% of the photosynthesis in green beans [22], while ash reduced up to 90% of the rate of photosynthesis of apple trees [23]. Nanos and Ilias [24] described the effects of cement dust, such as a reduced stomatal conductance and transpiration rate of olive trees. Similarly, Shukla et al [25] reported that the highly alkaline nature of the cement dust resulted in the reduced chlorophyll content of dusted plants.…”
mentioning
confidence: 99%
“…Introduzindo poeira de cimento em talhões de Pinus sylvestris à guisa de adubação, Kloseiko;Tilk (2006) comprovaram, após dois meses, que a acidez do solo e os parâmetros fotossintéticos medidos por fluorescência da clorofila não foram afetados pelos tratamentos, mas estes reduziram significativamente a concentração de hexoses em acículas de um ano de idade. Diminuição dos níveis totais de clorofila e da relação a:b, rebaixando a taxa fotossintética e a produção de plantas de oliveira expostas a poeira de cimento foram relatados por Nanos;Ilias (2007). Embora plantas do deserto (Zygophyllum prismatocarpum) tenham sido afetadas pela deposição de poeira, diminuindo o teor de clorofila, inibição da assimilação de CO 2 e do transporte de elétrons, van Heerden et al (2007) concluem que tais sintomas são reversíveis pela lavagem da poeira provocada pela chuva.…”
Section: Introductionunclassified